1995
DOI: 10.5694/j.1326-5377.1995.tb138404.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Burch colposuspension for stress incontinence: preliminary results

Abstract: ObjectiveTo assess the safety, effectiveness and potential benefits of laparoscopic Burch colposuspension. DesignNon‐randomised prospective study. SubjectsFifteen women, presenting consecutively with uro‐dynamically confirmed urinary stress incontinence. ResultsThe operation was successfully completed with no perioperative morbidity in 14 women. One woman subsequently underwent laparotomy after injury to the inferior epigastric artery. The average duration of surgery was 110 minutes, postoperative catheter‐isa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…In addition, this approach has shown no rise in the complication rate [2,27,28,30,31,33,40]. Before embracing this procedure, however, it is important to assess the cost implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this approach has shown no rise in the complication rate [2,27,28,30,31,33,40]. Before embracing this procedure, however, it is important to assess the cost implications.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1992 this particular operation has been routinely performed laparoscopically by one of the surgeons at Strathfield Private Hospital. In an earlier paper this surgeon reported upon the advantages of the laparoscopic approach: easier access, improved magnified view, minimal intraoperative blood loss, shorter length of stay, and earlier return to normal lifestyle [27]. Other reports in the literature have also proven laparoscopic colposuspension to have similar advantages [2,31,33,40].…”
mentioning
confidence: 93%
“…Applying laparoscopic technique to the surgical solutions for stress urinary incontinence has, as with its other applications, reduced tissue trauma, helped eliminate the pain related to wound healing, and decreased the time required for hospitalization and recovery [6,7]. To evaluate the clinical effect of laparoscopic Burch colposuspension, we report here our experience with 54 patients with stress urinary incontinence who were treated with the laparoscopic Burch procedure and the use of mesh reinforcement.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] A review of 113 LCs, by Cooper et al (1996), 15 found a subjective success rate of 87%. However, the mean duration of follow up was only 8.4 months.…”
Section: Discussionmentioning
confidence: 97%